Lembaga suaka dalam hukum internasional - Hamid, Sulaiman, 1947-; United Nations. General Assembly (Jakarta : Divisi Buku Perguruan Tinggi, RajaGrafindo Persada, 2002)
Legal protection for refugees according to international law
Includes the texts of: Universal Declaration of Human Rights, Convention against Torture and Other Cruel, Inhuman, or Degrading Treatment or Punishment (1984), and Convention Relating to the Status of Refugees (1951)
Includes bibliographical references (p. 103-106)
Keywords: Refugees -- Legal status, laws, etc